5G Enabling Technologies and Wireless Networking - Mackay, Michael (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The ongoing deployment of 5G networks is a key enabler for realizing upcoming services at scale, including the massive deployment of the Internet of Things, providing communications to support autonomous vehicles, and supporting the realization of smart cities. However, as the limitations of existing approaches become apparent, the need for next-generation technologies is growing, in terms of improving spectral efficiency, increasing network data rates and densification, supporting local/wide area wireless coordination, and more. In this Special Issue, we present some technologies to meet these demanding requirements and facilitate coordinating wireless networks to support future Beyond 5G networks.